THE EXPRESSIVE SKILLS OF THE POETRY OF SAINT ANONYMOUS: संत बेनामी जी के काव्य का अभिव्यंजना-कौशल - Kumar, Satish (International Journal of Research -GRANTHAALAYAH, 2017)
The Bhava Paksha (expression expression) and Kala Paksha (expression expression party) of any literature are essentially accepted. In the emotional aspect or expression aspect, the creator brings his spirit to the masses. In other words, if we can say that, the message that the creator wants to convey to the society through his creation is considered to be the expression side. It is a known fact that every composition has a purpose. This objective is based on the perfection of the emotional aspect. Bhava Paksha is considered an essential part of any composition. किसी भी साहित्य के भाव पक्ष (अभिव्यक्ति पक्ष) और कला पक्ष (अभिव्यंजना-पक्ष) अनिवार्यतः स्वीकार किए गए हैं। भाव पक्ष अथवा अभिव्यक्ति पक्ष मंे रचनाकार अपने भावांे को जनमानस तक पहुँचाता है। दूसरे शब्दांे, में यदि कहें तो यह कह सकते हैं कि रचनाकार अपनी रचना के माध्यम से जो संदेश समाज को देना चाहता है, उसे ही अभिव्यक्ति पक्ष माना जाता है। यह विदित तथ्य है कि प्रत्येक रचना का कोई न कोई उद्देश्य अवश्य होता है। यह उद्देश्य भाव पक्ष की पूर्णता पर ही आधारित होता है। भाव पक्ष किसी भी रचना का अनिवार्य अंग माना जाता है।